Effects of Gait Training With Body Weight Support on a Treadmill Versus Overground in Individuals With Stroke - Gama, Gabriela L.; Celestino, Melissa L.; Barela, Jose A. [UNESP]; Forrester, Larry; Whitall, Jill; Barela, Ana M. (Elsevier B.V., 2017)
Objective: To investigate the effects of gait training with body weight support (BWS) on a treadmill versus overground in individuals with chronic stroke. Design: Randomized controlled trial. Setting: University research laboratory. Participants: Individuals (N=28) with chronic stroke (>6mo from the stroke event). Interventions: Participants were randomly assigned to receive gait training with BWS on a treadmill (n=14) or overground (n=14) 3 times a week for 6 weeks. Main Outcome Measures: Gait speed measured using the 10-meter walk test, endurance measured using the 6-minute walk test, functional independence measured using the motor domain of the FIM, lower limb recovery measured using the lower extremity domain of the Fugl-Meyer assessment, step length, step length symmetry ratio, and single-limb support duration. Measurements were obtained at baseline, immediately after the training session, and 6 weeks after the training session. Results: At 1 week after the last training session, both groups improved in all outcome measures except paretic step length and step length symmetry ratio, which were improved only in the overground group (P=.01 and P=.01, respectively). At 6 weeks after the last training session, all improvements remained and the treadmill group also improved paretic step length (P<001) but not step length symmetry ratio (P>.05). Conclusions: Individuals with chronic stroke equally improve gait speed and other gait parameters after 18 sessions of BWS gait training on either a treadmill or overground. Only the overground group improved step length symmetry ratio, suggesting a role of integrating overground walking into BWS interventions poststroke. (C) 2016 by the American Congress of Rehabilitation Medicine
Keywords: Assistive technology; Clinical protocols; Exercise therapy; Rehabilitation